Investigative activities as promoters of argumentation in science teaching (Research, Society and Development, 2022)
The capacities to interpret and assess statements are very important for the formation of critical citizens, in a century marked by the dissemination of biased information loaded with distortions of scientific knowledge.  Scientific literacy (SL), in this context, is of great importance and needs to be promoted in the classroom. For this, or knowledge of the epistemology of science can contribute a lot to the entire structure of SL referring to ‘learning to make science’ and the argumentation is inserted in that axe. Also, to promote argumentation in the classroom, we apply an investigative activity in the first year of the high school, in emergency remote learning. The students constructed hypotheses that explain the phenomenon investigated and, then, went invited to negotiate with their colleagues from the group, at a better explanation.  As a result, we observed that students, in small discussion groups, have little initiative for an argument and that, even when oriented towards consensus, they be more concerned with an explanation to give to the teacher, who discuss the relevance you give explanations presented. The moments in which the students are effectively engagement into discussing strengths and weaknesses explanations, they concentrated on discussing with the whole group, since the teacher promoted the debate through questions seek further clarification on the affirmative of students. These results reinforce the importance of the teacher in the scaffolding and orientation of investigative activities and as a facilitator of epistemic practices of science in the classroom for promotion of students’ SL.